2021
DOI: 10.1186/s40170-021-00243-y
|View full text |Cite
|
Sign up to set email alerts
|

RNF115 promotes lung adenocarcinoma through Wnt/β-catenin pathway activation by mediating APC ubiquitination

Abstract: Background Patients with lung adenocarcinoma (LUAD) have high mortality rate and poor prognosis. The LUAD cells display increased aerobic glycolysis, which generates energy required for their survival and proliferation. Deregulation of Wnt/β-catenin signaling pathway induces the metabolism switching and oncogenesis in tumor cells. RING finger protein 115 (RNF115) is an E3 ligase for ubiquitin-mediated degradation. Although the oncogenic functions of RNF115 have been revealed in breast tumor cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 40 publications
(46 reference statements)
0
18
0
Order By: Relevance
“…TRIM25 takes part in tumor growth, metastasis, and chemoresistance with its ubiquitin ligase activities [ 18 , 44 ]. RNF115 is correlated with the prognosis of patients with lung adenocarcinoma or invasive breast cancer [ 45 , 46 ]. As a master regulator of DNA repair, dysfunction of TRAIP is associated with tumor development and progression [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…TRIM25 takes part in tumor growth, metastasis, and chemoresistance with its ubiquitin ligase activities [ 18 , 44 ]. RNF115 is correlated with the prognosis of patients with lung adenocarcinoma or invasive breast cancer [ 45 , 46 ]. As a master regulator of DNA repair, dysfunction of TRAIP is associated with tumor development and progression [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The RAB proteins are small GTPases that play essential roles in intracellular vesicle trafficking (55)(56)(57). Specifically, RAB7 is involved in late endocytic traffic and lysosome acidification as well as (41,42) Lung cancer inhibition cancer cell growth induction ubiquitination and degradation of cMyc (43) Gastric cancer promotation cancer cell growth interaction and stablization SNX7 to promote autophagosome maturation (52) mitochondria-lysosome contact (38). It is observed that overexpression of RNF115 promotes the late endosomelysosome fusion and acidification and the trafficking of HIV-1 viral particles to the lysosomes for degradation (15,39,44), whereas knockdown of RNF115 leads to the retention of EGFR in the late endocytic compartments and hyper-phosphorylation and stabilization of EGFR (27).…”
Section: Rnf115 In Intracellular Trafficking and Autophagosomal Matur...mentioning
confidence: 99%
“…The reason behind the discrepancies is unclear. However, it has been shown that RNF115 promotes lung adenocarcinoma by targeting p53, APC and c-Myc for ubiquitination and degradation, indicating complicated roles of RNF115 in lung cancer (41)(42)(43). RNF115 is expressed in all renal oncocytoma cases and in cases designated as oncocytic neoplasm which favor oncocytoma but barely expressed in renal cell carcinoma (60).…”
Section: Prognosis and Therapeutic Values Of Rnf115 In Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Wnt signal abnormalities are associated with some tumor disease, and the most significant ones are lung cancer, breast cancer, bladder cancer, clear cell renal cell cancer and prostate cancer ( Xu et al, 2022 ; Xue et al, 2022 ; Zhao et al, 2022 ). Most investigation on Wnt signaling pathway in lung adenocarcinoma only focus on Wnt pathway as a downstream signaling pathway to regulate the proliferation and differentiation of lung adenocarcinoma cells ( Tammela et al, 2017 ; Wu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%